C++ Data Structures and Algorithms Learn how to write efficient code to build scalable and robust applications in C++. - Anggoro, Wisnu (Packt Publishing, 2018)
C++ is a general-purpose programming language which has evolved over the years and is used to develop software for many different sectors. This book will be your companion as it takes you through implementing classic data structures and algorithms to help you get up and running as a confident C++ programmer.